UPAYA MUSYAWARAH GURU MATA PELAJARAN (MGMP) TINGKAT KABUPATEN UNTUK MENINGKATKAN KOMPETENSI GURU SENI TARI JENJANG SLTP DI KABUPATEN GUNUNGKIDUL (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This research aims to gain an overview about the effort of cultural arts meetings subject teacher (MGMP) in the district level to improve the competence of dance teacher in junior high school in Gunungkidul district includes program planning and MGMPs activities, MGMPs organization, MGMPs financing and also the result of MGMPs activities. The MGMPs activities such as : (1) Regular meeting; (2) Workshop about making of KTSP; (3) Singles dance work workshop; (4) ICT workshop; (5) Workshop lesson study; (6) Staging and performance; etc.This research use descriptive qualitative research approach with case studies in MGMPs cultural art in junior high school in Gunungkidul district. Data collection methods used are observation, interviews and documentation. Data analysis use descriptive narrative analysis with checking data by triangulation.The result of the research showed that MGMP can improve the competence and professionalism of dance teachers such as : (1) Pedagogical competence is ability of a teacher in the management of student learning; (2) The social competence is the ability of teachers in the field of information technology as a part of the community; (3) Professional competence is the ability of teacher in mastering the science about the field of arts when teaching.The impact of teacher professional development includes : (a) Quality of servive-learning is more fun and meaningful for students in order to achieve national education standards and potential development of national culture-based in order to have a global advantage; (b) Able to lift the quality of education by art, so well in the district and national levels.